NILAI SOLUSI PENDEKATAN SISTEM LINEAR SKALA BESAR MENGGUNAKAN GMRES - dkk, Farikhin (MATEMATIKA, 2008)
Many engineering process require the solution of linear system of the form , where A is a nonsingular real matrix, , and vector is solution of the linear system. There are two methods for solving large scale linear system which are full orthogonalization method (FOM) and Generalized minimal residual (GMRES). GMRES is most popular method to solve large scale linear equations. In this paper, we proven that GMRES preserved the magnitude of approximations solution of linear system.